A phytopharmacological review on alternanthera ficoidea - Pandey S.; Pal A.K.; Sahu A.N.; Nandi M.K. (My University, 2025)
The spine of Ayurveda and other traditional system of medicines is medicinal plants. The medicinal plants and their extracts are rich with minerals, primary metabolites and secondary metabolites, which are the effective against various diseases. India has big biodiversity that rich with medicinal plants and near about 2500 medicinal plants of Indian origin are recommended in traditional treatment for various diseases. In recent decades metabolites derived from the extract of medicinal plants are frequently used by allopathic physicians as cardio-vascular, immunomodulatory, anticancer and antibiotic medicines. One of the Indian medicinal plant, Alternanthera ficoidea (L.) (Synonyms: Alternanthera tenella Colla and Gomphera ficoidea) belongs to family Amaranthaceae. The plant is traditionally used as diuretic, anti-pyretic, antiseptic, anti-inflammatory and anti- diarrheal agent etc. The secondary metabolites like tannins, saponins, phytols, carotenoids and polyphenols are major classes of compounds are identified for the plant. Some phytomolecules are isolated from the extract as vitexin, quercetin, kaempferol, amarantin, betaine, isoamarantin and sterol etc. Pharmacological activities like hypolipidemic, anti-inflammatory, antidiabetic, antibacterial and immunomodulatory activity are also investigated on this plant. This study compile the information related to Alternanthera ficoidea, which will helpful the researchers for further study on this plant. © 2019, Advanced Scientific Research. All rights reserved.